2019
DOI: 10.1155/2019/1431384
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Thyme and Rosemary on Prevention of Osteoporosis in Rats

Abstract: Osteoporosis poses an important public health problem which affects millions of people worldwide. There is a direct link between calcium deficiency in diet and induction of osteoporosis and bone loss. The current study was conducted to evaluate the protective effect of thyme (Thymus vulgaris L.) and rosemary (Rosmarinus officinalis L.) against osteoporosis in rats with low calcium intake. Essential oils of rosemary and thyme were analyzed. The experiment was carried out on growing male Sprague–Dawley rats; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 79 publications
2
15
0
7
Order By: Relevance
“…In Europe, people have used rosemary as a spice of folk medicine for a long time. In recent study, it has been revealed that rosemary has many physiological functions such as improving memory (Farr et al, ), antioxidant (Ho, Wang, Wei, Huang, & Huang, ), anti‐inflammation (Rocha et al, ), and antiosteoporosis (Elbahnasawy, Valeeva, El‐Sayed, & Rakhimov, ). Furthermore, it is reported that rosemary contains PPARγ agonists such as carnosic acid, carnosol (Rau et al, ), and rosmaric acid (Han et al, ), which are suggested to contribute to the glucose‐lowering or anti‐inflammatory effects of rosemary.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, people have used rosemary as a spice of folk medicine for a long time. In recent study, it has been revealed that rosemary has many physiological functions such as improving memory (Farr et al, ), antioxidant (Ho, Wang, Wei, Huang, & Huang, ), anti‐inflammation (Rocha et al, ), and antiosteoporosis (Elbahnasawy, Valeeva, El‐Sayed, & Rakhimov, ). Furthermore, it is reported that rosemary contains PPARγ agonists such as carnosic acid, carnosol (Rau et al, ), and rosmaric acid (Han et al, ), which are suggested to contribute to the glucose‐lowering or anti‐inflammatory effects of rosemary.…”
Section: Introductionmentioning
confidence: 99%
“…Tratamiento de enfermedades parasitarias en peces, promotor del crecimiento e inmunoestimulante en peces, fumigante natural contra plagas, así como en el control y tratamiento de la caspa. (Ebrahimi et al, 2020) (Borges et al, 2018) (Karim et al, 2017 (Endo et al, 2018) (Zoral et al, 2018) (Ebrahimi et al, 2020) (Nieto et al, 2018) (Karadağ et al, 2019) (Ali et al, 2019) (Selmi et al, 2017) (Sadeh et al, 2019) (Ferreira et al, 2020) (Elbahnasawy et al, 2019) (Akhbari et al, 2018) (de Oliveira et al, 2019 (Ahsaei et al, 2019) (Trupti & Gadekar, 2018).…”
Section: Extracción De Metabolitos Secundarios Del Romero (R Officinunclassified
“…Insecticida y antifúngico. Control de plagas en la agricultura, así como en el control y tratamiento de la caspa (Sadeh et al, 2019) (Borges et al, 2018) (Ali et al, 2019) (Selmi et al, 2017) (Ferreira et al, 2020) (Elbahnasawy et al, 2019) (Trupti & Gadekar, 2018).…”
Section: Metabolitos Presentes En El Romerounclassified
See 2 more Smart Citations